Tolerância de microrganismos a herbicidas residuais utilizados na cultura do eucalipto - Rabelo, Jordana Stein (2022)
Competition with weeds is one of the main factors that limit the development of most forest species. Some herbicides used to control these plants have a residual effect in soil and cause environmental damage. Bioremediation appears as an alternative to decontaminate these areas. Therefore, the objective of this study was to evaluate the tolerance and degrading potential of herbicides that have a residual effect on eucalyptus crops by Aspergillus niger, Penicillium pinophilum and Trichoderma sp. and to evaluate the tolerance of bacteria Bacillus subtilis, Pseudomonas sp. and Azospirillum brasilense to these herbicides. The herbicides used were indaziflam, sulfentrazone, sulfentrazone +diuron, clomazone, glyphosate+s-metolachlor. The analysis of the tolerance of microorganisms to herbicides and the degrading potential was carried out in Czapek Dox medium, and in the second experiment the sources of carbon and nitrogen were removed. The evaluation of fungal growth was made by determining the biomass. The analysis of bacterial tolerance to herbicides was carried out in Luria Bertani medium in ELISA plates with evaluation of growth by optical density at 620 nm. The data was applied to the Gompertz model for evaluating the bacterial growth as a function of time in the presence of herbicides. In the tolerance analysis of microorganisms to herbicides, it was observed that all fungi are tolerant to the herbicides studied, with an increase in the growth of Trichoderma sp. in the presence of glyphosate+s-metolachlor. Thus, the analysis of the degrading potential was carried out only for Trichoderma sp. in the presence of the mixture of herbicides that potentiated its growth. In this analysis, there was no effect of herbicides on fungal growth; the fungus was unable to use the carbon present in the herbicide to enhance its growth; and there was no significant effect of nitrogen in the presence of the herbicide. By observing the tolerance analysis of the bacteria, through the parameters of the model used, it was concluded that the growth of Azospirillum brasilense, Bacillus subtilis and Pseudomonas sp. was not influenced by the presence of herbicides, thus demonstrating that the evaluated products do not affect the growth of bacteria. It is concluded, therefore, that the tested residual herbicides do not interfere with the development of the evaluated beneficial microorganisms.